Transit-Oriented Development (TOD): An approach to revitalize the Gateway City of Lowell, MA - Gopalan Narayanan, Shravanthi. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Christine Cousineau, and Shan Jiang.; Keywords: Transportation, and Urban planning.